Peningkatan Kemampuan Berbicara Anak Usia Dini Melalui Percakapan Sehari-hari - Sapriani Sapriani; Syamsiah Depalina (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2025)
This study aims to analyze how everyday conversations can significantly improve early childhood speech. The main focus of this research is the importance of environmental stimulation and the quality of interaction between children and adults, such as parents and teachers, in the process of language development. This research uses a descriptive qualitative approach with data collection techniques through direct observation and in-depth interviews with teachers and parents of early childhood. The results showed that daily interactions such as storytelling, question and answer activities, and structured games can significantly expand children's vocabulary, improve the sentence structure used, and increase children's confidence in communicating. Verbal activities that are carried out consistently and purposefully are proven to have a positive impact on the development of speaking skills. In conclusion, quality daily conversations play a central role in optimizing children's speaking skills from an early age, and are an important foundation for overall language development.